Selective Isolation of Bifidobacterium From Human Faeces Using Pangenomics, Metagenomics, and Enzymology - Yang, Shuanghong; Xie, Xinqiang; Ma, Jun; He, Xingxiang; Li, Ying; Du, Mingzhu; Li, Longyan; Yang, Lingshuang; Wu, Qingping; Chen, Wei; Zhang, Jumei (Frontiers in Microbiology, 2021)
Bifidobacterium, an important genus for human health, is difficult to isolate. We applied metagenomics, pangenomics, and enzymology to determine the dominant glycoside hydrolase (GH) families of Bifidobacterium and designed selective medium for Bifidobacterium isolation. Pangenomics results showed that the GH13, GH3, GH42, and GH43 families were highly conserved in Bifidobacterium. Metagenomic analysis of GH families in human faecal samples was performed. The results indicated that Bifidobacterium contains core GHs for utilizing raffinose, D-trehalose anhydrous, D(+)-cellobiose, melibiose, lactulose, lactose, D(+)-sucrose, resistant starch, pullulan, xylan, and glucan. These carbohydrates as the main carbon sources were applied for selective media, which were more conducive to the growth of bifidobacteria. In the medium with lactose, raffinose and xylan as the main carbon sources, the ratio of cultivable bifidobacteria to cultivable microorganisms were 89.39% ± 2.50%, 71.45% ± 0.99%, and 53.95% ± 1.22%, respectively, whereas the ratio in the ordinary Gifu anaerobic medium was only 17.90% ± 0.58%. Furthermore, the species significantly (p < 0.05) varied among samples from different individuals. Results suggested that xylan might be a prebiotic that benefits host health, and it is feasible to screen and isolate bifidobacteria using the oligosaccharides corresponding to the specific GHs of bifidobacteria as the carbon sources of the selective media.